Entre la miel y la misión: Desarrollo, cosmologías indígenas y fe práctica entre los awajún y wampis - Di Fonzo, Valerio (Pontificia Universidad Católica del Perú, 2025)
This ethnographic article explores how a beekeeping project promoted by the Jesuit NGO SAIPE in Awajún and Wampis communities of the Peruvian Amazon becomes a site of negotiation between indigenous cosmologies, kinship structures, sustainability expectations, and institutional logics of development and Jesuit missionary practice. Through a situated narrative across the villages of Ideal and Soledad, the article examines daily tensions involving gender, labor, markets, and collective organization. Far from being a mere productive initiative, beekeeping emerges as a moral and political field where the Jesuit work tradition, local aspirations, and the dilemmas of translating communal systems into donor-friendly formats intersect. The article suggests understanding such projects not as failures or successes, but as unstable and creative forms of world-making.

Este artículo etnográfico examina cómo un proyecto de apicultura promovido por la ONG jesuita SAIPE en comunidades Awajún y Wampis de la Amazonía peruana se convierte en un campo de negociación entre cosmologías indígenas, estructuras de parentesco, expectativas de sostenibilidad y lógicas institucionales de desarrollo y la praxis misionera jesuita. A través de una narrativa situada que recorre los pueblos de Ideal y Soledad, se analizan tensiones cotidianas relacionadas con el género, el trabajo, el mercado y la organización colectiva. Lejos de ser un simple emprendimiento productivo, la apicultura se revela como un espacio moral y político donde confluyen la tradición de trabajo jesuita, las aspiraciones locales y los dilemas que surgen al traducir sistemas comunales en formatos legibles para donantes y estados. El texto propone entender estas iniciativas no como éxitos o fracasos, sino como formas inestables y creativas de ensamblaje entre mundos.
Between Honey and Mission: Development, Indigenous Cosmologies, and Practical Faith among the Awajún and Wampis
Keywords: Peruvian Amazon; Beekeeping; Sustainable development; Jesuit missions; Awajun; Wampis; Amazonía peruana; Apicultura; Desarrollo sostenible; Misiones jesuitas; Awajún; Wampis; https://purl.org/pe-repo/ocde/ford#5.04.03